Iron-catalyzed domino coupling reactions of π-systems - Pounder, Austin; Tam, William (Beilstein Journal of Organic Chemistry, 2021)
The development of environmentally benign, inexpensive, and earth-abundant metal catalysts is desirable from both an ecological and economic standpoint. Certainly, in the past couple decades, iron has become a key player in the development of sustainable coupling chemistry and has become an indispensable tool in organic synthesis. Over the last ten years, organic chemistry has witnessed substantial improvements in efficient synthesis because of domino reactions. These protocols are more atom-economic, produce less waste, and demand less time compared to a classical stepwise reaction. Although iron-catalyzed domino reactions require a mindset that differs from the more routine noble-metal, homogenous iron catalysis they bear the chance to enable coupling reactions that rival that of noble-metal-catalysis. This review provides an overview of iron-catalyzed domino coupling reactions of π-systems. The classifications and reactivity paradigms examined should assist readers and provide guidance for the design of novel domino reactions.
Keywords: cascade; catalysis; coupling; earth-abundant; iron